Construcción de soporte metálico móvil para sistema solar fotovoltaico (2023)
The work developed is focused on the second methodology. In this it is sought that the entire photovoltaic panel is kept in perpendicular position to the solar radiation source of light, which will be done by manual addressing of the base of the solar panel.